2018
DOI: 10.1007/jhep09(2018)140
|View full text |Cite
|
Sign up to set email alerts
|

Gauged six-dimensional supergravity from warped IIB reductions

Abstract: We find a family of complete non-linear Kaluza-Klein reduction ansätze from type IIB supergravity to Romans' 6D F (4) gauged supergravity in the bosonic sector. The reduction is over a sphere S 2 and a Riemann surface Σ, and depends on a pair of arbitrary locally holomorphic functions A ± on Σ. This family of reductions is inspired by the recent construction of 1/2 BPS supersymmetric warped AdS 6 solutions of IIB supergravity that depend on these same functions A ± .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(91 citation statements)
references
References 46 publications
(87 reference statements)
2
89
0
Order By: Relevance
“…In [36] it was shown that six-dimensional F (4) gauged supergravity is a consistent nonlinear Kaluza-Klein reduction of the warped AdS 6 solutions of type IIA massive supergravity. Recently an analogous statement has been shown [26,27] for the warped AdS 6 × S 2 solutions of type IIB supergravity found in [12,13,14]. The fact that such a consistent truncation exists implies that any solution of F (4) gauged supergravity can be lifted to ten-dimensional solutions, which have precise holographic duals.…”
Section: F (4) Gauged Supergravitysupporting
confidence: 58%
See 1 more Smart Citation
“…In [36] it was shown that six-dimensional F (4) gauged supergravity is a consistent nonlinear Kaluza-Klein reduction of the warped AdS 6 solutions of type IIA massive supergravity. Recently an analogous statement has been shown [26,27] for the warped AdS 6 × S 2 solutions of type IIB supergravity found in [12,13,14]. The fact that such a consistent truncation exists implies that any solution of F (4) gauged supergravity can be lifted to ten-dimensional solutions, which have precise holographic duals.…”
Section: F (4) Gauged Supergravitysupporting
confidence: 58%
“…In this paper we consider a simpler system, namely Romans' six-dimensional F (4) gauged supergravity [25]. Recent results [26,27,28] show that any solution of this six-dimensional theory can be uplifted and embedded in the general IIB solutions of [12,13,14]. This implies that the solutions in this paper lift to ten-dimensional holographic defect solutions.…”
Section: Introductionmentioning
confidence: 98%
“…The results presented here therefore support the AdS 6 /CFT 5 dualities proposed in [35,36] for 5d SCFTs engineered by 5-brane junctions, and the dualities proposed in [45,47,53] for AdS 6 solutions with 7-branes [37]. The Type IIB supergravity description for the 5d SCFTs considered here on a family of squashed spheres with −φ 1 = φ 2 = φ 3 = i √ 1 − s 2 can be obtained with the consistent truncations from the Type IIB solutions of [35][36][37] to 6d gauged supergravity worked out in [50,51,54]. Namely, by uplifting the 6d solutions of [72,73].…”
Section: Discussionmentioning
confidence: 60%
“…Type IIB supergravity solutions describing the near-horizon limits of 5-brane webs and 5-brane webs with 7-branes have been constructed in [34][35][36] and [37], 1 and result in large classes of explicit holographic dualities for the corresponding 5d SCFTs. Various aspects of the dualities have been studied in [43][44][45][46][47][48][49][50][51][52][53][54][55][56]. In particular, the free energy was found to scale quartically with the parameter controlling the large-N limit in supergravity [43], and this scaling was confirmed numerically using field theory methods [48,56].…”
Section: Introductionmentioning
confidence: 93%
“…It has long been known that this particular theory is a consistent truncation of D = 10 massive type IIA supergravity [35]. Note that it is also established more recently that this theory can be uplifted to IIB supergravity as well [36][37][38]. For definiteness we will consider in this article uplifts to massive IIA 1 , where the relevant brane interpretation is as D4-branes in the presence of D8-branes.…”
Section: Introductionmentioning
confidence: 88%